STRATEGI DIVISI MEDIA BRANDING DALAM OPTIMALISASI PUBLIKASI DAN CITRA DPMA IPB - Auliya Asyifa Rozen; Sutisna Riyanto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the media branding division's strategy in optimizing the publication and Image of the Directorate of Agromaritime Community Development (DPMA IPB), focusing on its goal to be active, credible, and innovative. Utilizing a qualitative approach through active participation observation and in-depth interviews, the research was conducted within DPMA IPB. The findings indicate that the Division's strategic efforts to project its institutional Identity (Melewar, Foroudi, & Jin, 2020) have encountered a significant Image gap. This gap is primarily due to two constraints: the low readership rate of articles and a monotonous and overly formal writing style. This failure to transform technical material into engaging narratives directly resulted in low audience Engagement (low page views), suggesting the institutional message was not effectively delivered. The study concludes that achieving a credible Reputation requires the Division to intensify its narrative strategies (storytelling) and implement a robust data-based evaluation system to validate the public's perception and optimize the institutional image.